Faktor - Faktor yang Mempengaruhi Konsumsi Bahan Pangan di Daerah Istimewa Yogyakarta - Indah Widowati (Jurnal Dinamika Sosial Ekonomi, 2000)
he welfare level indicator of a household or population is the expenses allocation. The poorer of a household or population in a region, the higher expenses allocation for food. Howefer, the household expenses relatively in proportion to family income. The objectives of the research is to determine the factors influence the allocation of the household income for the food consumption. The expenses for consuming rice was affected by the hedonic price of cassava, family income and the amount of the family members. The parameter of cassava and corn hedonic prices is positive, means that the cassava and corn are rice substitution. The expenses for consuming cassava was affected by hedonic price of cassava, family income and location. The parameter of rice and com hedonic price is negative. means that the rice and corn are cassava complementary. The expenses for consuming corn was affected by hedonic price of corn, family income, the amount of the family members and location. The parameter of rice and cassava hedonic prices is positive, means that the rice and cassava are com substitution.Key words: Consumption, hedonic price, foodstuffs